Distribuição espacial e perfil químico de Chaetocarpus schomburgkianus (Kuntze) Pax & Hoffmann (Peraceae) no Parque Nacional do Viruá, Roraima - Prado, Edmar da Silva (2013)
The present study describes the bark chemical profile of a dioecious tree Chaetocarpus schomburgkianus (Kuntze) Pax & Hoffmann (Peraceae) along a soil texture gradient ranging from 16 to 58% of clay. The study was conducted in six Biodiversity Research Program (PPBio) permanent plots located in Viruá National Park (Caracaraí RR). To construct the chemical profile, we collected bark samples of 18 individuals, 9 males and 9 females. From each individual selected, outside the fertile period, we collected a sample of bark. Sex was defined through the observation of floral structures during the reproductive period. To characterize the environment around each individual, four soil samples at the canopy projection area were collected at 0-10 cm and 10-20 cm of depth. Samples were mixed forming a composite one for each depth. Soil samples were analyzed for texture and fertility, and the data were summarized by a Principal Component Analysis. The extract of the bark of C. schomburgkianus indicated the presence of flavonoids, saponins and tannins, but did not detect steroids and triterpenoids. The presences of secondary compounds were not related to sex, or to soil characteristics. We found intra-specific variation in the intensity of flavonoids, but this variation was also not related to soil characteristics (pH, texture and fertility) or the sex of the individual.